Korean Wave's Influence on BT21 Purchases in Indonesia: Pengaruh Korean Wave terhadap Pembelian BT21 di Indonesia - Putri, Rachelita Agista Nasruhan; Hariasih, Misti (Universitas Muhammadiyah Sidoarjo, 2024)
The influence of Korean Wave Brand Ambassadors and Influencers on purchasing decisions for BIS